PELAYANAN BANTUAN BADAN PENYELENGGARA JAMINAN SOSIAL TERHADAP KELUARGA MISKIN DI KELURAHAN BULUROKENG KECAMATAN BIRINGKANAYA KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
Poverty is one of the major social problems in Makassar City, precisely in Bulurokeng Village, Biringkanaya District. One of the efforts to tackle poverty is the existence of a government program for free health insurance, commonly known as the Health Insurance Administration Agency (BPJS). Therefore, this research was conducted to find out how the service process was carried out by the Social Service during the administration of Health Insurance for the poor. This research is qualitative research with a social research approach that is used as a reference in analyzing the object under study in accordance with the science of logic by using the methods of observation, interviews, and documentation. Data analysis was also carried out in four stages, namely data analysis, data reduction, data presentation, and withdrawal of verification/conclusion. The results of the study indicate that the process of providing Social Security assistance services from the Social Service to the Kelurahan and the community is directed at the following processes: 1) File Receipt. 2) The Department of Social Affairs must first trace the people who have registered to get the free guarantee. 3) Validate data. 4) Card distribution. In the service process, supporting and inhibiting factors are often found. Among the supporting factors are 1) Targeting 95% of Makassar people to be covered by Universal Health Coverage (UHC). 2) Clarity of service information. 3) Completeness of Facilities and Infrastructure. 4) Human resources. While the inhibiting factors are 1) It is difficult to sort out people who have been able to. 2) The length of the process of making a health insurance card. 3) Lack of public awareness about the importance of health insurance. Keywords: Service, Poverty, BPJS.